MEMBUKA JENDELA PANTUN KEHIDUPAN: SUATU REFLEKSI KEGELISAHAN IBERAMSYAH BARBARY DALAM BERKARYA - NFN Saefuddin (Kantor Bahasa Provinsi Gorontalo, 2020)
Iberamsyah Barbary has a peculiarity in his work. He packages it by giving color about daily life and Indonesian taste.There is anxiety that can be seen in his work.The problem which is discussed in this study is how does the reflection form of Iberamsyah Barbary’s concern seeing modern life in his environment. This study aims to reveal the kind of reflection form of Iberamsyah Barbary’s concern about seeing modern life in his environment. As one of the literary man, he pays attention to presenting his thought through his works, for example, quatrains that have modern life nuance and have lots of massages and the first line of the quatrain. Iberamsyah Barbary’s work seems not to lecture someone but it contains entertainment aspects for the readers. This study uses a descriptive qualitative method. It is a method to get information deeply about quatrain analysis by Iberamsyah Barbary through the analysis of first-line quatrain and the content. The result shows the description about the reflection form of Iberamsyah Barbary’s concern seeing modern life through quatrain